WHO IS THE DOCTOR? COMPARISON OF PHYSICIAN REPRESENTATIONS BETWEEN MEDICAL ACADEMIC AND SUS USERS - Letícia Zanutim; Mayara Macedo Trindade; Nathália Dell Eugênio Costa; Lila Maria Spadoni Lemes (UniEVANGÉLICA, 2016)
Objectives: to know the social representation of medical and compare it among medical students of the fourth year and users of the Unified Health System ( SUS). Methods: this study used a field survey by questionnaire with open and closed questions Results: social representation of the doctor is different for the groups. Conclusion: The research concluded that for medical students the doctor is a professional and responsible worker and SUS users entered in the Family Health Strategy is a medical health professional. It also concluded that the patient is no longer passive against the health-disease process and seeks always know their rights and collect them . With this, even the biomedical model is no longer satisfactory making room for the biopsychosocial model .